1997
DOI: 10.1103/physrevd.55.2708
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive dissociation in the interacting gluon model

Abstract: We have extended the interacting gluon model to calculate diffractive mass spectra generated in hadronic collisions. We show that it is possible to treat both diffractive and nondiffractive events on the same footing, in terms of gluon-gluon collisions. A systematic analysis of available data is performed. The energy dependence of diffractive mass spectra is addressed. They show a moderate narrowing at increasing energies. Predictions for CERN LHC energies are presented. ͓S0556-2821͑97͒06703-9͔

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 6 publications
(34 citation statements)
references
References 44 publications
(50 reference statements)
1
33
0
Order By: Relevance
“…Its original application to the description of inelasticity [12] and multiparticle production processes in hydrodynamical treatments [13] was followed by more refined applications to leading charm production [14] and to single diffraction dissociation, both in hadronic reactions [15] and in reactions originated by photons [16]. These works allowed for providing the systematic description of the leading particle spectra [17] and clearly demonstrated that they are very sensitive to the amount of gluonic component in the diffracted hadron as observed in [18] and [19].…”
Section: A Brief History Of the Igmmentioning
confidence: 99%
See 4 more Smart Citations
“…Its original application to the description of inelasticity [12] and multiparticle production processes in hydrodynamical treatments [13] was followed by more refined applications to leading charm production [14] and to single diffraction dissociation, both in hadronic reactions [15] and in reactions originated by photons [16]. These works allowed for providing the systematic description of the leading particle spectra [17] and clearly demonstrated that they are very sensitive to the amount of gluonic component in the diffracted hadron as observed in [18] and [19].…”
Section: A Brief History Of the Igmmentioning
confidence: 99%
“…In Ref. [15] we have shown that the introduction of the above metioned cuts drastically reduces the energy ( √ s) dependence of the diffractive mass distributions leading, in particular, to the approximate 1/M 2 X behaviour for all values of √ s from ISR to Tevatron energies. Here these cuts produce another type of scaling, which may be called "projectile scaling" or "projectile universality of the diffractive peak" and which means that for large enough x L the diffractive peak is the same for all projectiles.…”
Section: Translated To Leading Pion or Proton Production This Means Tmentioning
confidence: 99%
See 3 more Smart Citations